The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3174/ajnr.a6768
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenting and Mechanical Thrombectomy in Patients with Acute Ischemic Stroke and Tandem Occlusions: Antithrombotic Treatment and Functional Outcome

Abstract: BACKGROUND AND PURPOSE: There is no consensus on the optimal antithrombotic medication for patients with acute ischemic stroke with anterior circulation tandem occlusions treated with emergent carotid stent placement and mechanical thrombectomy. The identification of factors influencing hemorrhagic risks can assist in creating appropriate therapeutic algorithms for such patients. This study aimed to investigate the impact of medical therapy on functional and safety outcomes in patients treated with carotid ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
(37 reference statements)
2
27
1
1
Order By: Relevance
“…26 In a study recently reported by our group, we found that emergency stenting is safer in defined circumstances, including intraprocedural heparin avoidance, baseline ASPECTS > 8, and a straightforward MT with a first-pass complete recanalization. 27 In the present study, we confirmed the safety and efficacy of emergency stenting in TOs irrespective of ECL etiology, without differences in terms of sICH risk between the two groups. However, we found that only patients with CA-related TOs showed a better 3-month outcome after emergency stenting.…”
Section: Emergency Stentingsupporting
confidence: 83%
“…26 In a study recently reported by our group, we found that emergency stenting is safer in defined circumstances, including intraprocedural heparin avoidance, baseline ASPECTS > 8, and a straightforward MT with a first-pass complete recanalization. 27 In the present study, we confirmed the safety and efficacy of emergency stenting in TOs irrespective of ECL etiology, without differences in terms of sICH risk between the two groups. However, we found that only patients with CA-related TOs showed a better 3-month outcome after emergency stenting.…”
Section: Emergency Stentingsupporting
confidence: 83%
“…A previous report showed that a heparin dose of 3000 IU administered during the EVT intervention for TL was a significant predictor of sICH,25 while in our study patients did not receive heparin during the EVT.…”
Section: Discussioncontrasting
confidence: 58%
“…Based on the latest antiplatelet Delphi consensus, aspirin IV (500 mg bolus) should be used as the first-line agent prior to carotid stenting [22]. Although Da Ros et al identified potential predictors for sICH as the higher intraprocedural heparin dosage, the initial ASPECTS ≤7 and the MT needs more than one attempt for complete recanalization [26]. However, differences were not observed in our study, probably due to the significantly lower number of sICH cases, the different periprocedural heparin management, and the lack of detailed MT attempts data (only the presence of first pass effect was documented).…”
Section: Discussionmentioning
confidence: 99%